2013
DOI: 10.1371/journal.pone.0062397
|View full text |Cite
|
Sign up to set email alerts
|

Human Vocal Attractiveness as Signaled by Body Size Projection

Abstract: Voice, as a secondary sexual characteristic, is known to affect the perceived attractiveness of human individuals. But the underlying mechanism of vocal attractiveness has remained unclear. Here, we presented human listeners with acoustically altered natural sentences and fully synthetic sentences with systematically manipulated pitch, formants and voice quality based on a principle of body size projection reported for animal calls and emotional human vocal expressions. The results show that male listeners pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
82
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 38 publications
9
82
2
1
Order By: Relevance
“…Xu, Kelly, & Smillie 24 extended this theory and proposed a bio-informational dimensions (BID) theory, which contains body-size projection, dynamicity, audibility and association. Experimental evidence confirms that BID-based acoustic features such as F0, formant spacing, voice quality and pitch range encoding dominance in male voices and compliance in female voices are perceived to be attractive 5 . Another explanation would be the averageness theory, which states that attractive faces and voices are close to the population mean 25 26 .…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Xu, Kelly, & Smillie 24 extended this theory and proposed a bio-informational dimensions (BID) theory, which contains body-size projection, dynamicity, audibility and association. Experimental evidence confirms that BID-based acoustic features such as F0, formant spacing, voice quality and pitch range encoding dominance in male voices and compliance in female voices are perceived to be attractive 5 . Another explanation would be the averageness theory, which states that attractive faces and voices are close to the population mean 25 26 .…”
Section: Introductionmentioning
confidence: 60%
“…Meanwhile, there is cross-linguistic variation in the effect of certain acoustic parameters on perceived vocal attractiveness. For example, a narrow pitch range benefits male vocal attractiveness in British English 5 , whereas studies on Japanese reported that the opposite is true 14 . Within the same language, results from studies by different researchers can greatly disagree too.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from communication through verbal content, paralinguistic elements of the voice during speech enable individual recognition and assessment of the speaker's physical characteristics such as sex (Puts, Apicella, & Cárdenas, 2012), body size (Feinberg, Jones, Little, Burt, & Perrett, 2005;Xu, Lee, Wu, Liu, & Birkholz, 2013), physical strength (Sell et al, 2010), femininity (Feinberg, 2008;Feinberg, Jones, DeBruine, et al, 2005), attractiveness (Feinberg, Jones, Little, et al, 2005;Feinberg, Jones, DeBruine, et al, 2005;Xu et al, 2013), conception risk (Pipitone & Gallup, 2008), and sexual maturity (Mulac & Giles, 1996). In humans, perceived attractiveness and mate quality can be manipulated by artificially lowering the pitch of male voices or artificially increasing it in female voices, commensurate with sex-typical vocal properties (Collins, 2000;Feinberg, Jones, Little, et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…From an experimental perspective, Xu et al (2013) show that hearers rate breathy voices in both men and women as more attractive. Speakers with attractive voices in turn receive more support during social interactions (Sarason, 1985), which would explain why the use of breathy voice may be advantageous in the development of a question prosody.…”
Section: Cross-linguistic Context -From Speaker-centred Back To Hearementioning
confidence: 97%